Auditory compensation for head rotation is incomplete - Freeman, Tom; Culling, John; Akeroyd, Michael A.; Brimijoin, W. Owen (American Psychological Association, 2016)
Hearing is confronted by a similar problem to vision when the observer moves. The image motion that is created remains ambiguous until the observer knows the velocity of eye and/or head. One way the visual system solves this problem is to use motor commands, proprioception and vestibular information. These ‘extra-retinal signals’ compensate for self movement, converting image motion into head-centred coordinates, though not always perfectly. We investigated whether the auditory system also transforms coordinates by examining the degree of compensation for head rotation when judging a moving sound. Real-time recordings of head motion were used to change the ‘movement gain’ relating head movement to source movement across a loudspeaker array. We then determined psychophysically the gain that corresponded to a perceptually-stationary source. Experiment 1 showed that the gain was small and positive for a wide range of trained head speeds. Hence listeners perceived a stationary source as moving slightly opposite to the head rotation, in much the same way that observers see stationary visual objects move against a smooth pursuit eye movement. Experiment 2 showed the degree of compensation remained the same for sounds presented at different azimuths, although the precision of performance declined when the sound was eccentric. We discuss two possible explanations for incomplete compensation, one based on differences in the accuracy of signals encoding image motion and self-movement, and one concerning statistical optimisation that sacrifices accuracy for precision. We then consider the degree to which such explanations can be applied to auditory motion perception in moving listeners.